Laccase Facilitated Synthesis of Silver Nanoparticles for Biomedical, Biocontrol and Dye Degradation Applications - M.O, Kazeem; A.P , itilope; A.B, Agbaje; G.E, Ogunleye (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Green synthesis of various metallic nanoparticles has gained significant attention in recent years due to their numerous applications. Laccase synthesis of silver-nanoparticles (AgNPs), characterization and applications were investigated. The synthesized AgNPs were characterized using UV-visible spectroscopy, FTIR, SEM and EDS. Antimicrobial activity of the synthesized AgNPs against Escherichia. coli, Staphylococcus aureus, Colletotrichum sp., Fusarium sp., Penicillum and Aspergillus niger was studied. Disease suppression capability of AgNPs on chili pepper and pear fruits were monitored by visual observation. A yellow to brown colour change and surface plasmon resonance peak at 407 nm indicated AgNPs formation. The FTIR spectra of the AgNPs reveals the appearance of distinctive bands, SEM analysis showed a particle size (20 nm-100 nm) with spherical morphology while EDS reveals a strong signal in the silver region and confirm the formation of AgNPs. The AgNPs showed growth inhibition of bacteria (33-42%), fungi (12-33%) and dyes degradation (25-63%). Furthermore, effective disease suppression was observed on pear and chili pepper fruits. This study described the synthesis of AgNPs using laccase from A. carbonarious and emphasizes its role in disease suppression and industrial dye degradation.